The Political Economy of Energy Alteration in Indonesia: The Role of Coal and Mineral in New and Renewable Energy Alteration - Hartanto, Hartanto (Journal of International Relations on Energy Affairs, 2021)
The world's energy sources have seen various transformations, with the majority first relying on biomass such as firewood to satisfy their energy demands, before transitioning to fossils such as coal, oil, and natural gas as a result of the industrial revolution. Indonesia, like other rising market nations, faces issues in satisfying its domestic energy demand. Dependence on fossil energy sources presents its own challenges. This study is focused on the constraints associated with green growth policy in East Kalimantan. The purpose of this paper is to address three questions: first, to reiterate the importance of developing more comprehensive energy transition strategies in Indonesia. This is accomplished by comparing data on the availability of energy sources to data on Indonesia's expanding energy demands. Second, how to establish an energy transfer policy that takes into consideration Indonesia's conditions and potentials, as well as the problems that must be solved. Third, how to position the mining and coal sector as a key component of the energy transformation process, especially given the long-term character of the transformation process, while reaching energy sufficiency is a problem that demands immediate attention. To discuss this, the author uses qualitative methods with case studies. The results showed that in general, a number of prerequisites need to be met to make coal and nickel a transitional element, namely: infrastructure, resources, economic aspects, and national energy policies. To increase the contribution of New and Renewable Energy in the National Energy Mix, there are still a number of problems and challenges, both from the policy and regulatory aspects to support the development of NRE, the aspect of providing accurate data, the financial aspect for developing NRE for private investors, and the aspect of providing technology and infrastructure to support private investment in the NRE sector.